Natural capital preservation in the coastal area - Runko Luttenberger, Lidija (Array, 2018)
The removal of a single tree growing in an urban area or a patch of forest for development purposes is a practice that results from inappropriate economic approach to and unawareness of the value of natural capital and the services it provides. The paper analyses the benefits of the existence of urban trees and discusses valuation methods, emphasizing in particular the value of vegetation in the coastal area of the Republic of Croatia. Due to holistic focus of the topic, a qualitative research is applied based on observations, authors’ previous research, experiences, reports on current research and legislation. Several instruments for the preservation and maintenance of vegetation are proposed ranging from the measures by local self-governments, upgrading the system of fees for forest general benefit functions to proper implementation of non-financial reporting which should apply to all companies whose operations may have an impact on natural capital, regardless of their size and ownership structure. National legislation should meet more than a minimum compliance with EU directives and international efforts in standardizing non-financial reporting. Many companies undertake activities that may and do exert pressure on vegetation cover or natural capital, as do also the entities of public interest such as local and regional self-government units and the companies established by them, which should also become liable to non-financial reporting.